2020
DOI: 10.3390/nu12030778
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies Following Minimally Invasive Esophagectomy for Cancer

Abstract: Over the past decades, survival rates for patients with resectable esophageal cancer have improved significantly. Consequently, the sequelae of having a gastric conduit, such as development of micronutrient deficiencies, become increasingly apparent. This study investigated postoperative micronutrient trends in the follow-up of patients following a minimally invasive esophagectomy (MIE) for cancer. Patients were included if they had at least one postoperative evaluation of iron, ferritin, vitamins B1, B6, B12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Oral supplementation is advised in the preoperative setting for both patients with EC and GC, while postoperative advice regarding monitoring of micronutrients and additional micronutrient supplementation for these patients is lacking 27. However, literature investigating malnutrition after oesophageal or gastric surgery shows that malnutrition and suboptimal micronutrient intake is highly prevalent 13–15. Moreover, current evidence shows that a thorough understanding of the postoperative micronutritional needs and treatment of micronutrient deficiencies for these patients is necessary 12 27 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral supplementation is advised in the preoperative setting for both patients with EC and GC, while postoperative advice regarding monitoring of micronutrients and additional micronutrient supplementation for these patients is lacking 27. However, literature investigating malnutrition after oesophageal or gastric surgery shows that malnutrition and suboptimal micronutrient intake is highly prevalent 13–15. Moreover, current evidence shows that a thorough understanding of the postoperative micronutritional needs and treatment of micronutrient deficiencies for these patients is necessary 12 27 28…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported micronutrient and macronutrient deficiencies after both oesophagectomy for EC and gastrectomy for GC 13–15. Deficiencies were found in 60%–78% of the study population.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, iron oxidation has been shown to contribute to tumor formation and subsequent cancer development ( Torti and Torti, 2013 ). On the other hand, several studies reported that iron deficiency may enhance the risk of developing cancer ( Janssen et al, 2020 ). Anemia, low serum ferritin levels, and autoimmune gastritis–related iron malabsorption were identified as risk factors associated with gastrointestinal tumors and GC ( Nomura et al, 1992 ; Cover et al, 2013 ; Kamada et al, 2021 ).…”
Section: Iron Metabolism In Gastric Cancermentioning
confidence: 99%
“…Patients with cancer of the upper GI tract are not only at risk of developing nutritional deficiencies and weight loss prior to surgery, but also after surgical treatment [12][13][14][15]. Underlying reasons for this are malabsorption, malnutrition and reduced food intake [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anemia following esophagectomy is common and anemia-related symptoms like fatigue or dyspnea can impair the patient's quality of life [12,20]. Reasons for postoperative anemia in upper GI cancer patients are diverse.…”
Section: Introductionmentioning
confidence: 99%